Risk Seeking Moderates the Association Between Emotion Dysregulation and Cannabis-Related Consequences. (July 2019) - Kentopp, Shane D.; Johnson, Nicholas; Fresquez, Cara; Prince, Mark A.; Conner, Bradley T.; ,
Sensation seeking and emotion dysregulation have been identified as contributing factors for consequences associated with cannabis use, although findings have been mixed. The study seeks to clarify relations between sensation seeking, emotion dysregulation, and cannabis-related consequences. Cannabis users ( N = 2, 128) were assessed for facets of sensation seeking, emotion dysregulation, and cannabis-related consequences. Results revealed a positive association between risk seeking and cannabis-related consequences, as well as between emotion dysregulation and cannabis-related consequences. A negative association was observed between experience seeking and cannabis-related consequences. An interaction was found between emotion dysregulation and risk seeking. Risk seeking appears to be a risk factor for cannabis-related consequences at lower levels of emotion dysregulation. At high levels, the effect of emotion dysregulation superseded that of risk seeking. These findings have implications for the prioritization of clinical concerns in individuals seeking treatment for problematic cannabis use.